Review of Witness Testimony and Right of Defense: Canon 1598 - Manzelli, Michael (CLSA advisory opinions, 2001-2005, 2001)
A person gave witness testimony in a marriage nullity case before an ecclesiastical tribunal, under the tacit understanding that the parties in the case would not be told or shown what the witness had either said or written. Notified of the publication of the acts of the case, the respondent, who had cooperated. throughout the proceedings, requested to review the testimony offered in the case. After various attempts at non-compliance with the law concerning the publications of the acts, the tribunal allowed the respondent to review the testimony. As a result of this review by the respondent the witness sued the tribunal in civil court, for failure to inform him about the consequences of his giving testimony, as well as for breach of confidence. The witness argued that he was given to understand that what he had said or had written would be used only to assist the tribunal in reaching a decision.